2015
DOI: 10.4172/2157-2518.1000217
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Tumorigenesis and Clinical Implications of Viral Infection in Breast Cancer

Abstract: The prevalence of breast cancer is rising worldwide. The main cause of death from breast cancer is distant metastasis, which occurs within 3 years after diagnosis in 10-15% of patients. The initiation and progression of breast cancer have been related to both external and internal factors, including viral infection. Human cytomegalovirus infection (HCMV) is common in breast cancer and metastases, and high tumor levels of HCMV appear to worsen outcomes. HCMV can increase the malignant behavior of tumor cells by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 112 publications
0
1
0
Order By: Relevance
“…CMV is a member of herpesviridae family and infects a major part of the human population with lifelong persistence (14). CMV replicates in a spectrum of human cells, especially endothelial cells and macrophages, and may produce latency infection (15). Regarding the possible mechanisms involved in CMV carcinogenesis, it has been reported that immediate-early protein (IE) 86 prevents the inhibitory functions of pRb, resulting in the release of E2F and induction of cell cycle (16).…”
Section: Introductionmentioning
confidence: 99%
“…CMV is a member of herpesviridae family and infects a major part of the human population with lifelong persistence (14). CMV replicates in a spectrum of human cells, especially endothelial cells and macrophages, and may produce latency infection (15). Regarding the possible mechanisms involved in CMV carcinogenesis, it has been reported that immediate-early protein (IE) 86 prevents the inhibitory functions of pRb, resulting in the release of E2F and induction of cell cycle (16).…”
Section: Introductionmentioning
confidence: 99%